ANALISIS DAYA PENGGERAK KINERJA KARYAWAN (Studi Kasus Perawat Rumah Sakit Jiwa Grhasia DIY) - Constantino Lobato Isasias (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
Abstract This study aims to determine and analyse the influence fomenting of employee performance. Subject of the research are nurse of ghrasia mental hospital Special Region Yogyakarta. Data used are validity and reliability by using Software SPSS 17.0 series, then for testing indicators and test hypotheses and test path analysis using analytical tools SmartPLS 3. The results of this study are 1) Working Environment variable proven effect on motivation with test parameter value 0.278 and a P value of  0.007 Values. 2) Variable Job Satisfaction proven effect on motivation with test parameter value 0.623 and a P value of  0.000 Values. 3) Variable Work motivation is not proven effect on performance with test parameter value 0.064 and a P value of 0.793 Values. 4) Work Environment Variables not proven effect on performance with test parameter values of -0,304 and the value of  P Values  0.153. 5) Job Satisfaction Variables is not proven effect on performance with test parameter values of -0,067 and the value of P as  0.773. Keywords: working environment, job satisfaction, work motivation, performance